Emerging trends in tourism - National Seminar on "Tourism in India: Challenges Ahead" (2009 : Business School, University of Jammu); Aima, Ashok; Chauhan, Vinay; Bhasin, Jaya.; University of Jammu. Business School (New Delhi : Excel Books, 2011)
Contributed research papers presented at a National Seminar on "Tourism in India: Challenges Ahead", March 06-07, 2009, organised at The Business School, University of Jammu under Special Assistance Programme.
Includes bibliographical references.
Keywords: Tourism -- India -- Congresses